2015
DOI: 10.2176/nmc.ra.2014-0386
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Timings of Re-operation for Residual or Recurrent Hemifacial Spasm after Microvascular Decompression: Personal Experience and Literature Review

Abstract: We reviewed reports about the postoperative course of hemifacial spasm (HFS) after microvascular decompression (MVD), including in our own patients, and investigated treatment for delayed resolution or recurrence of HFS. Symptoms of HFS disappear after surgery in many patients, but spasm persists postoperatively in about 10–40%. Residual spasm also gradually decreases, with rates of 1–13% at 1 year postoperatively. However, because delayed resolution is uncommon after 1 year postoperatively, the following is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
(63 reference statements)
1
9
0
1
Order By: Relevance
“…These measurements correspond to most NVC sites of HFSs, which have been accepted as the sites where the rational pathogenetic mechanism is triggered. However, some subsequent reports have indicated that NVC in the distal cisternal portion of the facial nerve also causes HFS (Hatayama et al, 2015; Ryu et al, 1998; Son, Ko, & Choi, 2019). Thus, this hypothesis is still incomplete and further discussion is required.…”
Section: Discussionmentioning
confidence: 99%
“…These measurements correspond to most NVC sites of HFSs, which have been accepted as the sites where the rational pathogenetic mechanism is triggered. However, some subsequent reports have indicated that NVC in the distal cisternal portion of the facial nerve also causes HFS (Hatayama et al, 2015; Ryu et al, 1998; Son, Ko, & Choi, 2019). Thus, this hypothesis is still incomplete and further discussion is required.…”
Section: Discussionmentioning
confidence: 99%
“…However, TN recurs slightly more frequently than does hemifacial spasm. 4,12, 21,22 The reasons for recurrence or partial pain remission of TN are variable. Factors, such as Teflon granuloma formation and venous compression, have commonly been involved in the redevelopment of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence represents symptoms reappearing postoperatively after a symptom-free interval of more than 1 year [34]. When there is no improvement or worsening of symptoms after one year postoperatively, it is called “incomplete cure” or persistence [34, 35]. Reasons for an unsuccessful MVD include incomplete decompression by not identifying the true culprit vessels, presence of a previously unidentified secondary offending vessel, or implant compression/migration against the facial nerve [3638].…”
Section: Discussionmentioning
confidence: 99%